Demand for Freight Transport : Practical Results of Studies on Market Operation - Bayliss, Brian T.; European Conference of Ministers of Transport (Paris : European Conference of Ministers of Transport, 1973)
One of the constant aims of transport research policy is to devise methods applicable in concrete cases. In the monograph, one of such methods is the modal-split analyses. Two basic reasons for this method is that it can be of the market research type where it is intended to establish the importance of various factors in choice of mode; and of a forecasting exercise where the aim is to forecast future flows of traffic by the different modes for planning purposes.
At head of title: Economic Research Centre.
Includes bibliographical references.
ne 27/02/2018
Loan
Keywords: Freight and Freightage; Choice of Transportation